Evaluation of stress indices for screening of rice cultivars for high temperature tolerance - N, Veronica; Y, Ashoka Rani; D, Subrahmanyam; KL, Narasimha Rao; M, Lal Ahamad; P, Prasuna Rani; P, Yugandhar (ORYZA-An International Journal of Rice, 2019)
High temperature during the crop growing period is detrimental as it results in reduction of yield. A diverse set of rice germplasm consisting of 60 genotypes was grown at two different sowing times (normal and late) and were exposed naturally to high temperature in the late sown condition (stress). There was a severe reduction in grain yield and spikelet fertility in all the genotypes in the late sown crop. Yield based indices were computed based on grain yield  recorded under normal and stress conditions. Indices Stress Susceptibility Index (STI), Geometric Mean Production (GMP), Mean Production (MP), Yield Index (YI), Modified stress tolerance (K1STI and K2STI) were positively correlated with yield recorded under both normal and high temperature stress condition and can be considered as suitable indices for screening of rice genotypes under high temperature conditions. Ranking genotypes based on the indices revealed that Rasi, HKR47, IR64, Khudaridhan, Akshayadhan and N22 exhibited the highest mean rank and hence they can be identified as heat-tolerant genotypes. ADT43, Vandana, IR36, MTU1001, ADT49 and Krishnahamsa had a lower rank and were identified as susceptible genotypes to high-temperature stress.